Disparitas Sosial dan Ekonomi dalam Novel Hari Terakhir di Rumah Bordil Karya Bode Riswandi: Kajian Sosiologi Sastra - Ayuningtyas, Aulia Gita; Mila Maulidiyah; Nita Khairunnisa; Ichsan Fauzi Rachman (BADAN PENERBIT STIEPARI PRESS, 2024)
This research was motivated by the findings of socio-economic disparities in the novel Hari Terakhir di Rumah Bordil. This research aims to reveal disparities as a result of analysis using a literary sociology approach. The type of research used is descriptive analysis. The data collection techniques are reading, writing, listening, processing and data techniques. The research subject is the novel 'Last Day in a Brothel' with the research object of social disparities. The results of the research are based on analysis of the data obtained, namely the discovery of social events with negative labeling, society's bad insults towards female prostitutes, and the impasse of working honorably due to elementary school (SD) graduate education as well as economic inequality that means a person has social control over himself and others. is the value of the money owned.